Food and nutritional security analysis for the diversity of farming systems in Southern Bangladesh - Lopez-Ridaura, Santiago; Zepeda, Adair; Amjath-Babu, Tharayil Shereef; Aravindakshan, Sreejith; Shrestha, Robin; Shibani, Ghosh; Webb, Patrick; Krupnik, Timothy Joseph (CIMMYT, 2025)
Farms are supposed to provide food for the family members through self-consume and trade. This can be explored with the Nutritional Adequacy Ratio (NAR). However, not all farms have the same characteristics, and face different food constraints in their local context. The estimation of the NAR highlights nutritional risks for family, and for long-term rural development. In this study the potential NAR was measured for different regions of Bangladesh at North, West and South regions.